Locking and Control: A Door Bolt Sealing from Hierakonpolis - Bussmann, Richard.
The paper discusses an unpublished door bolt sealing from Hierakonpolis excavated in 1978. The sealing pattern belongs to a visual tradition originating in the predynastic period. The proposed reconstruction of the locking system combines analysis of the reverse side of the sealing with archaeological evidence of doors and door bolts. Public performance is suggested for sealing practice and control to function socially.